#TITLE_ALTERNATIVE# - EKA PUTRA (NIM 19009090) pembimbing : Ir. Subiakto Soekarno, MBA, RFA, CHANDRA
The main topic of this thesis is building an optimal portfolio of mutual funds. The mutual funds used for this research are from First State Investments Indonesia. Nowadays, there are people who want to invest in the capital market but they lack of time, skills, and experience in it. So, to overcome this problem, mutual fund is created. Mutual fund is a product consists of many capital market instruments like stocks and bonds funded by investors’ fund and managed by investor manager. With mutual fund, investors can save time and energy to invest in the capital market. The problem is, can one of these mutual funds can top the market average returns or not. The market stated before is JCI or Jakarta Composite Index. According to the author calculation, none of these mutual funds can top the average daily return of the market. The only way to overcome this problem is to construct a portfolio of those mutual funds. So the goal of this thesis is to construct an optimal portfolio based on Markowitz’s modern portfolio theory from First State Investments Indonesia’s mutual funds. The time horizon of this thesis is from the beginning of 2009 until the end of 2011. There are 3 optimal portfolios that have been created. Those 3 are Maximum Return portfolio, Minimum Stadev portfolio, and Maximum Sharpe Ratio portfolio. The creation of those 3 portfolios was helped by the MS Excel Solver add-ins to determine the weights of each mutual fund in a portfolio. Then those 3 portfolios compared to each other and the market with some performance measurements like Sharpe ratio, Treynor ratio, and Jensen’s Alpha. The calculation creates a result that the best performance achieved from those 3 portfolios is the Maximum Sharpe Ratio portfolio because the portfolio generates the highest Sharpe ratio. The highest Sharpe ratio according to Markowitz is the most optimal portfolio. That portfolio exceeds the market in terms of performance with 0.0674% average daily return and 0.5640% average daily standard deviation. So the author suggests that investors to collect the mutual funds in Maximum Sharpe Ratio portfolio which contains 78.46% of FSI Bond fund, 13.12% of FSI Multistrategy fund, and 8.41% of FSI Sectoral fund because from 2009 until 2011 shows a good performance. For future studies or investments, the author suggests using a forecasted NAV, JCI’s closing prices, and BI rate so the result will be more accurate.